2015
DOI: 10.1051/0004-6361/201424965
|View full text |Cite
|
Sign up to set email alerts
|

The HARPS search for southern extra-solar planets

Abstract: We describe radial-velocity time series obtained by HARPS on the 3.60 m telescope in La Silla (ESO, Chile) over ten years and report the discovery of five new giant exoplanets in distant orbits; these new planets orbit the stars HD 564, HD 30669, HD 108341, and BD -114672. Their periods range from 492 to 1684 days, semi-major axes range from 1.2 to 2.69 AU, and eccentricities range from 0 to 0.85. Their minimum mass ranges from 0.33 to 3.5 M Jup . We also refine the parameters of two planets announced previous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 37 publications
6
29
0
Order By: Relevance
“…Feng et al 2015;Santerne et al 2016;Moutou et al 2015). The frequency of systems with long-period giant planets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al 2015;Santerne et al 2016;Moutou et al 2015). The frequency of systems with long-period giant planets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the orbital motion of exoplanets, through direct imaging (e.g., Chauvin et al 2012;Kalas et al 2013;Bonnefoy et al 2014;Nielsen et al 2014), or through indirect techniques such as radial velocity and transit measurements (e.g., Cumming et al 2008;Howard et al 2012;Marcy et al 2014;Moutou et al 2015), can provide a wealth of information about their properties, the processes through which they form, and how they interact dynamically with other bodies in the system. Accurately determining the orbital parameters of exoplanets can constrain their masses and densities (e.g., Charbonneau et al 2000) and lead either to the discovery of additional planets in the system (e.g., Nesvorný et al 2012), or to the exclusion of additional planets within a range of periods by invoking dynamical stability arguments (e.g., Correia et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2015b) found that 5 ± 5% of Kepler multi's have stellar companions at separation 1-100 au, compared to 21% for field stars in the solar neighborhood, suggesting that such companions can misalign or disrupt multi-planet systems. On the other hand, RV surveys continue to reveal a population of giant planets at large distances ( > ∼ a few au) from their host stars (e.g., Marmier et al 2013;Feng et al 2015;Moutou et al 2015;Rowan et al 2016;Wittenmyer et al 2016;Bryan et al 2016). The Keck survey suggests that about 20% of solar-type stars could host gas giants within 20 au (Cumming et al 2008), while HARPS finds that 14% of such stars host giant planets with periods less than 10 years.…”
mentioning
confidence: 99%